The response of a guyed transmission line system to boundary layer wind. (15th May 2017) - Hamada, A.; King, J.P.C.; El Damatty, A.A.; Bitsuamlak, G.; Hamada, M.
Highlights: Aeroelastic testing of multiple spans guyed transmission line system is conducted. No instabilities are observed for the tested transmission towers or lines. The aeroelastic model shows a quasi-static response to steady boundary layer wind loads. The Background response relative to the total response is between 4 and 59%. The Resonant peaks of the dynamic response are more noticeable in the low wind speeds. Abstract: The current study investigates the aeroelastic characteristics and structural response of a multiple-span guyed lattice transmission line system, through a simultaneous testing of four aeroelastic guyed lattice towers and conductors. The transmission line system simulated in the current study is a generic guyed transmission tower used by different hydro companies in North America and in different parts of the world. The aeroelastic model is designed for a geometry scale of 1:50 and tested in the Boundary Layer Wind Tunnel Laboratory at the University of Western Ontario, Canada. The model is tested using an open exposure wind profile. The aeroelastic test is performed for three different wind directions and for two configurations, with and without the transmission lines (conductors and ground-wires). Such aeroelastic model of guyed transmission line system with multiple-spans is not reported in literature. This represent a new contribution to the existing literature of the aeroelastic behaviour of transmission lines under wind actions. The study investigates the aeroelastic model response to boundary layer wind loading under different wind speeds and configurations. For the 37 wind speeds, two configurations, and three angles of attack used in the current aeroelastic test, no instabilities are observed for the tested transmission towers or lines. The measured natural frequencies of the aeroelastic model match those obtained by numerical modelling and those provided in the literature, and are affected by the value of the pretension force applied to the supporting guys. The results indicate that the multiple-span guyed transmission line system aeroelastic model responded in a quasi-static manner to boundary layer wind loads. Resonant dynamic response is less significant and becomes less distinguished by increasing the wind speeds. The results are used to understand the response of guyed transmission line systems to boundary layer wind loads.